CREATION OF OPTRONICS FOR APPLICATION IN OPTOELECTRONICS (Scientific journal of the Fergana State University, 2024)
The physical and technical foundations for creating high-performance optocouplers for microelectronics using polycrystalline inhomogeneous semiconductor membranes are described. The scientific basis for reducing energy losses observed in optocouplers is analyzed. In addition to the above, the efficiency of the optoelectronic device depends on the fact that the light signals reach the photo receiver intact with low losses in the optical photon-mediated connections between the elementary optron elements, the light source and its consumer. In a microelectronic system, this problem can be solved by means of fiber optics. Fiber optic devices are compact, their light fiber diameter is about 1 µm. High elasticity, its bending does not destroy the transmitted optical signal. The efficiency is much higher than that of electrical communication. The level of image transfer capability is high. To realize these advantages, the quality of the optical contact between the optical fiber and the light source and consumer must be high. To satisfactorily perform this task, the refractive index (n) of the immersion medium is taken to be close to the refractive index of the light source and the photoreceptor.